Sharp force - Cornwell, Patricia Daniels (Cornwell, Patricia Daniels. Scarpetta series., 2025)
"NO ONE IS SAFE FROM THE SERIAL KILLER NOT EVEN SCARPETTA... During the early hours of Christmas morning, chief medical examiner Dr. Kay Scarpetta receives a chilling call. The Phantom Slasher has struck again. The serial killer has terrorized Northern Virginia for months. His pattern is to stalk with a sophisticated technology that enables him to invade his victims' homes and watch their every move. They wake up to a ghost-like hologram before being murdered in their beds. Scarpetta is summoned to Mercy Island, the site of a notorious psychiatric hospital where two people have been brutalized, one of them from Scarpetta's past. It soon becomes apparent that she could be next..." --